2003
DOI: 10.1089/089771503767869962
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in the Vicinity of Brain Contusions: A Proton Magnetic Resonance Spectroscopy and Histology Study

Abstract: Proton MR spectroscopy (1H-MRS) has been previously used to monitor metabolic changes in areas of diffuse brain injury. We studied metabolism in the close vicinity of experimental traumatic brain contusions and remote on the contralateral side from 1h to 28d post-injury. Changes of creatine and phosphocreatine (Cr&PCr), N-acetylaspartate (NAA), choline (Cho), inositol (Ino), taurine (Tau), glutamate (Glu), and lactate (Lac) were assessed and compared to neuronal, glial and inflammatory changes in histology. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
88
2

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 62 publications
11
88
2
Order By: Relevance
“…Studies using MRSI in children also showed NAA/Cre reductions early after injury (10) as well as decreased NAA/Cho ratios up to three years post injury (36). Animal models of TBI that demonstrated decreases of NAA, found associations with regions of diffuse axonal injury (37) and neuronal loss (38,39). Therefore, the association of reduced NAA with poor cognitive outcome provides further evidence that NAA functions as a marker for neuronal and axonal injury in the setting of TBI in humans.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Studies using MRSI in children also showed NAA/Cre reductions early after injury (10) as well as decreased NAA/Cho ratios up to three years post injury (36). Animal models of TBI that demonstrated decreases of NAA, found associations with regions of diffuse axonal injury (37) and neuronal loss (38,39). Therefore, the association of reduced NAA with poor cognitive outcome provides further evidence that NAA functions as a marker for neuronal and axonal injury in the setting of TBI in humans.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, patients were imaged on average 6 Ϯ 4 days following injury, with some as long as 16 days after injury. Animal models have shown that metabolites such as Cho and mI increase soon after injury (38) whereas, NAA associated with neuronal dysfunction may remain depressed for days to weeks depending on the severity of injury (41) and may be permanent if neuronal loss has occurred (39). The time course for metabolic changes following TBI is not well established in humans and may vary by age as well as injury severity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, diffuse astrogliosis correlated with a decline in tNAA concentration, probably reflecting diffuse neuronal tissue degeneration. As m-Ins concentrations can be attributed to increased astroglial GFAP expression, m-Ins is probably an astroglial marker (25)(26)(27). Alterations in m-Ins concentrations in patients with TLE have been described previously (28,29).…”
Section: Discussionmentioning
confidence: 92%
“…Traumatic and ischemic brain injury triggers a large, transient increase in excitatory amino acid transmitter efflux in the brain of experimental animals and human subjects (2)(3)(4)(5)(6). Glutamate activation of the N-methyl-D-aspartate (NMDA) receptor (NMDAR), which is a ligand-gated ion (calcium and sodium) channel, results in channel opening and ion influx into the cell.…”
mentioning
confidence: 99%
“…Microdialysis studies of extracellular glutamate in human TBI and stroke patients suggested that the increase in glutamate in humans is more sustained [6 h to several days (7,8)] than in rodents, where it only lasts minutes (2)(3)(4)(5)(6). This result may have contributed to a decision to administer NMDAR antagonists in clinical trials of head injury for several days rather than once after severe nonpenetrating injury.…”
mentioning
confidence: 99%